العنف المدرسي وعلاقته بالتحصيل الدراسي لدى تلاميذ الطور الابتدائي -دراسة ميدانية لعينة من تلاميذ مدرسة قروم مخلوف ببلدية حمام الضلعة- - بن تركي راوية; اشراف: زعيتر لامية (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة إلى الكشف عن وجود علاقة ارتباطية بين العنف المدرسي بمختلف أنواعه (البدني واللفظي) والتحصيل الدراسي لدى تلاميذ مرحلة التعليم الابتدائي، وتحديدًا للصفوف الثالثة والرابعة والخامسة، جاءت أهمية الدراسة من الحاجة لفهم تأثير العنف على مستوى التحصيل الدراسي، مما يساعد في تطوير برامج تهدف إلى تقليل العنف وتعزيز السلوكيات الإيجابية، بالإضافة إلى تحسين البيئة التعليمية ودعم تعلم الطلاب. تكون مجتمع الدراسة من 139 تلميذًا وتلميذة، تم اختيارهم بطريقة عشوائية بسيطة. استخدمت الباحثة استبيانًا مكونًا من 35 بندًا مقسمًا إلى ثلاثة محاور: العنف البدني، العنف اللفظي، والتحصيل الدراسي. أظهرت نتائج الدراسة وجود علاقة ارتباطية واضحة بين العنف البدني والعنف اللفظي من جهة، والتحصيل الدراسي من جهة أخرى لدى تلاميذ التعليم الابتدائي، بناءً على النتائج أوصت الدراسة بضرورة تعزيز الوعي التربوي بخطورة العنف البدني واللفظي، وتكوين المعلمين في مجال إدارة السلوك التربوي، وإنشاء خلية إنصات ومرافقة نفسية داخل المدرسة، بالإضافة إلى إشراك الأسرة في مراقبة ومتابعة الوضع المدرسي للتلميذ. الكلمات المفتاحية: العنف المدرسي، التحصيل الدراسي، تلاميذ المرحلة الابتدائية. Abstract: This study aimed to investigate the existence of a correlational relationship between school violence, in its various forms (physical and verbal), and academic achievement among primary school students, specifically those in grades three, four, and five. The importance of the study stems from the need to understand the impact of violence on academic performance, which helps in developing programs aimed at reducing violence and promoting positive behaviors, as well as improving the educational environment and supporting student learning. The study population consisted of 90 male and female students, selected through a simple random sampling method. The researcher used a questionnaire consisting of 35 items divided into three sections: physical violence, verbal violence, and academic achievement. The study’s results showed a clear correlational relationship between both physical and verbal violence and academic achievement among primary school students. Based on these results, the study recommended raising educational awareness about the dangers of physical and verbal violence, training teachers in behavior management, establishing a listening and psychological support unit within the school, and involving families in monitoring and following up on the student’s academic situation. Keywords: school violence, academic achievement